Self Efficacy Relationship towards Improvement of Mother's Knowledge in Childhood Management with Diarrhea - A. Artifasari; Irawati Irawati (Journal La Medihealtico, 2020)
Diarrhea is a condition where a person experiences defecation more than 3 times a day with a watery consistency. The level of knowledge will affect the management of a disease as well as the self-confidence or self-efficacy that a person has. The purpose of this study was to determine the relationship between self-efficacy and maternal knowledge in the management of toddlers with diarrhea. In this study, sampling using the Accidental Sampling technique. This research was conducted by collecting sample data of 60 mothers who brought their children to posyandu (Integrated Service Post) either who were experiencing diarrhea or had had diarrhea through structured questions or research questionnaires using descriptive methodology. This study was measured using chi-square tests. Chi-square tests showed that the results of this study obtained a value of ρ value of 0.001 <0.05. So that H1 is accepted and H0 is rejected, which means that there is a relationship between maternal self-efficacy and knowledge in the management of toddlers with diarrhea in the Palakka Health Center, Bone Regency. Where if self-efficacy is low, the value of knowledge is also low. Self-efficacy or self-confidence has a positive influence on one's knowledge. There is a relationship between maternal self-efficacy and knowledge in the management of children under five with diarrhea in the Palakka Health Center, Bone District.